Is asexual reproduction more important at geographical limits? A genetic study of the seagrass Zostera marina in the Ria Formosa, Portugal - Billingham, M. R. (2014)
In populations of species that are able to reproduce both sexually and asexually, there may be local differences with regard to the relative importance of the 2 modes of reproduction. Studies of plant species with such a life history have shown that the contribution of sexual reproduction to population maintenance may be lower at the geographical margins, with genotypic diversity often used as an indicator of the relative importance of vegetative and sexual reproduction. This hypothesis was examined in a collection of samples of eelgrass Zostera marina (a marine flowering plant) from its eastern Atlantic southern limit (Ria Formosa, Portugal). Samples from 12 sites were genotyped using 9 microsatellite loci to compare within-site clonal and genetic diversity, and among-site distribution of genetic diversity, with previously published values from central sites. Sites within the Ria Formosa had lower clonal diversities (mean = 0.29, range = 0.07 to 0.68) than the central sites (mean = 0.86, range = 0.33 to 1.00), lower levels of expected heterozygosity (He = 0.423 vs 0.486) and exhibited heterozygote excesses rather than deficits. Similarly, genetic differentiation was found to be much greater in the Ria Formosa, with the FST of 0.233 being over 10-fold greater than that reported for populations in the Baltic Sea. Results from this study were consistent with previous findings of reduced sexual reproduction, genotypic diversity and among-population gene flow at species limits.